2012
DOI: 10.1590/s1413-81232012001100005
|View full text |Cite
|
Sign up to set email alerts
|

Regionalização e acesso à saúde nos estados brasileiros: condicionantes históricos e político-institucionais

Abstract: Regionalização e acesso à saúde nos estados brasileiros: condicionantes históricos e político-institucionaisRegionalization and access to healthcare in Brazilian states: historical and political-institutional conditioning factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
82

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(135 citation statements)
references
References 14 publications
3
50
0
82
Order By: Relevance
“…As this process developed, the success of national strategies for the organization of care networks, aimed at reducing fragmented health actions and services and promoting regionalization of the SUS, depended heavily on the political-institutional contexts of each federative unit 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As this process developed, the success of national strategies for the organization of care networks, aimed at reducing fragmented health actions and services and promoting regionalization of the SUS, depended heavily on the political-institutional contexts of each federative unit 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding regionalization as a technical-political process, conditioned by the supply capacity, healthcare financing, power distribution and relations established among the various stakeholders throughout the territories 8 , we observed that Ordinance Nº 4.279/10 and Decree Nº 7.508/11, in Minas face great challenges due to the various regional realities.…”
Section: Resultsmentioning
confidence: 96%
“…The implications of adopting decentralization as a guideline in the implementation of health systems and its relationship with sector reform movements have been pointed out in the national and international literature [1][2][3][4] . Analyzes about the municipalist realm of the Brazilian health system show diverse results and are strongly conditioned by the context of implementation, reflecting the realities of the municipalities and the political will of governmental stakeholders 1,5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Norms and guidelines were then published to give materiality to regionalization 2,5,7,8 . In this process, parameters were established to define territorial distribution (health regions) and interregional collegiates were established, with representatives of the different spheres of government responsible for conducting health policy at the regional level 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation